Tipe Hunian dan Jenis Mangsa Burung Serak Tyto alba javanica pada Ekosistem Persawahan - Retno Astuti K.; Soeprapto Mangoendihardjo; F. X. Wagiman; Djuwantoko Djuwantoko (Universitas Gadjah Mada, 2004)
The barn owl, Tyto alba javanica (Gmel.); is one of the important predator of rats. For controlling the rat population, the predator must retain in the rice ecosystem in which it is supported by continuous availability of its prey and suitable nest. The barn owl does not make its own nest, hence, the suaitable nest are necessary vailable in the ecosystem. The rat population fluctuatesand in the certain time it is difficult to find, hence, alternative preys have to be available. The nest type and prey species of the barn owl in the rice-field ecosystem had been survayed in Kendal District, Central Java Province, from October 2003 until March 2004. The area represented the rice-field ecosystem type with various habitats. The prey species were described from analysis of 2.261 pellets that were collected from 106 nests. The nests were found and distributed in 72 sub-sub district and in 17 subdistricts. Hairs, pulmes, skulls, teeth, obtained from the pellets were identified following the Hafidzi & Naim method (2003). The nest types consisted of building plafon (76,41%), trees (20,75%) and nest box (2,84%). Rats were the predominant prey-species (86,90%); consisted of Rattus argentiventer 77,08%, Rattus norvegicus 9,86%, Rattus rattus diardii 0,58%, Bandicota indica 0,01% and Rattus tiomanicus 0,005%),followed by aves (5,49%), insects (3,98%), bats (2,07%), and others (1,59%) i.e. squirrels, gecko, house-lizard, and frogs.